National parliaments and the new contentiousness of trade. Issue 7 (10th November 2017) - Roederer-Rynning, Christilla; Kallestrup, Morten
Abstract: Rather than becoming obsolete, national parliaments have come back obstinately in the politics of trade. This article develops this proposition and explores its contribution to the idea of twenty first-century trade as contentious market regulation. Contra the Lisbon Treaty, national parliaments' assertion entrenches the role of domestic actors in the EU trade liberalisation policy, and fleshes out its multi-level parliamentary bases. We discuss the role, drivers, and patterns of parliamentary assertion and explore parliamentary assertion using preliminary survey and case study material. We find that the Transatlantic Trade and Investment Partnership negotiations represented the tipping-point of parliamentary assertion. Through interpretation and political engagement, national parliaments have forged a role for themselves that was unforeseen in the Lisbon Treaty: weighing in on the policy-making and the ratification processes. In Europe, parliamentary assertion reflected the twin impact of a changing global trade agenda and the centralisation of the EU trade policy regime.